Support for Instructional Leadership - Johnston, William R. (RAND Corporation, 2016)
This report presents findings from a Wallace Foundation–funded survey of RAND’s American School Leader Panel, a nationally representative sample of principals, regarding the quantity, content, and perceived quality of on-the-job supports offered by districts to school leaders. It particularly examines how school leader support reflects the role of leadership in instruction and how school district size is related to support school leaders get.